2010
DOI: 10.1091/mbc.e10-05-0408
|View full text |Cite
|
Sign up to set email alerts
|

The γTuRC Revisited: A Comparative Analysis of Interphase and Mitotic Human γTuRC Redefines the Set of Core Components and Identifies the Novel Subunit GCP8

Abstract: We compared the composition of γ-tubulin ring complexes tandem-affinity purified from asynchronous and mitotic human cells by mass spectrometry. We identified various interactors including the novel core subunit GCP8. GCP8 is the first subunit with an interphase-specific role in centrosomal γ-tubulin recruitment and microtubule nucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 41 publications
6
109
0
1
Order By: Relevance
“…GCP5 and GCP6 are also present in stoichiometric amounts, but about three times less abundant than GCP2 or GCP3, and GCP4 is nearly twice as abundant as GCP5 and GCP6, but only half as abundant as GCP2 and GCP3. Finally, three proteins associated with the γ‐TuRC, Nedd1 (Haren et al , 2006; Luders et al , 2006) and Mozart 1, and Mozart 2 (Hutchins et al , 2010; Teixido‐Travesa et al , 2010) are similarly abundant as the GCP2 and GCP3 core components of γ‐TuSC. These data extend previous biochemical studies (Murphy et al , 2001; Choi et al , 2010) and support the notion that multiple γ‐TuSCs associate with GCP4, GCP5, and GCP6 into γ‐TuRCs (Kollman et al , 2011; Lin et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…GCP5 and GCP6 are also present in stoichiometric amounts, but about three times less abundant than GCP2 or GCP3, and GCP4 is nearly twice as abundant as GCP5 and GCP6, but only half as abundant as GCP2 and GCP3. Finally, three proteins associated with the γ‐TuRC, Nedd1 (Haren et al , 2006; Luders et al , 2006) and Mozart 1, and Mozart 2 (Hutchins et al , 2010; Teixido‐Travesa et al , 2010) are similarly abundant as the GCP2 and GCP3 core components of γ‐TuSC. These data extend previous biochemical studies (Murphy et al , 2001; Choi et al , 2010) and support the notion that multiple γ‐TuSCs associate with GCP4, GCP5, and GCP6 into γ‐TuRCs (Kollman et al , 2011; Lin et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…A missense mutation in GCP2 and downregulation of GCP4 have been shown to change the angle of microtubule branching in Arabidopsis (Nakamura and Hashimoto, 2009;Kong et al, 2010). Of note, human g-TURC was shown to interact with subunits of the chaperonin containing T-complex protein, suggesting that conformation of the nucleation complex may be actively regulated (Teixidó -Travesa et al, 2010). TON2, as a putative B99 subunit of the PP2A, may modulate the conformation of the g-TURC through regulating the phosphorylation status of one or more structural subunits.…”
Section: Ton2 Is a Regulator Of Microtubule Nucleationmentioning
confidence: 99%
“…These proteins localise a subpopulation of γ-tubulin to existing spindle MTs, and their absence leads to spindles of lower density with an increased astral population (Goshima et al 2008;Hughes et al 2008). Termed Augmin, or HAUS (homologous to Augmin subunits; Lawo et al 2009;Uehara et al 2009), this conserved hetero-octomeric complex has been shown to directly interact with the γTuRC subunit, NEDD1 (Zhu et al 2008), a result that has been independently verified (Teixidó-Travesa et al 2010). Thus, a model has been proposed in which Augmin binds existing spindle MTs during prometaphase and targets active γTuRC, facilitating intraspindle MT nucleation (Goshima et al 2008;Uehara et al 2009) (Fig.…”
Section: Augmin-generated Mtsmentioning
confidence: 98%